2011
DOI: 10.5194/angeo-29-2305-2011
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for heating electrons in the magnetopause current layer and adjacent regions

Abstract: Abstract. Taking advantage of the string-of-pearls configuration of the five THEMIS spacecraft during the early phase of their mission, we analyze observations taken simultaneously in the magnetosheath, the magnetopause current layer and the magnetosphere. We find that electron heating coincides with ultra low frequency waves. It seems unlikely that electrons are heated by these waves because the electron thermal velocity is much larger than the Alfvén velocity (V a ). In the short transverse scale (k ⊥ ρ i >>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…What remains is the kinetic Alfvén wave mode. This wave mode has significant perpendicular V and B fluctuations at low frequencies and a weak total pressure fluctuation (Chaston et al, ; Hollweg, ; Roux et al, ). This mode is presumed to be driven on field lines that resonate with global modes generated in the magnetosphere due to disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…What remains is the kinetic Alfvén wave mode. This wave mode has significant perpendicular V and B fluctuations at low frequencies and a weak total pressure fluctuation (Chaston et al, ; Hollweg, ; Roux et al, ). This mode is presumed to be driven on field lines that resonate with global modes generated in the magnetosphere due to disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that ion response alone does not maintain quasineutrality and that the corrugated drift wave has variation along B . Strong V e z motion is associated with intense E || at high frequencies [ Newman et al, ; Roux et al, ; Stawarz et al, ]. Since the bursts of E || have short durations (tens of milliseconds), it is possible that the observations in Figure i are not representative since they are averaged over 30 ms.…”
Section: Analysis and Model Of The Observed Wavesmentioning
confidence: 99%
“…Even with such small statistics, these observations suggest that asymmetric magnetic reconnection may be inherently turbulent. Furthermore, the low‐frequency B fluctuations and the strong E || fluctuations seem to be connected through strong field‐aligned currents [ Roux et al, ; Stawarz et al, ]. The low‐frequency B fluctuations and the strong E || fluctuations may influence magnetic reconnection.…”
Section: Introductionmentioning
confidence: 99%
“…The most common manifestation of the electromagnetic whistler-mode wave in the inner magnetosphere is the chorus wave within the frequency range 0.1-0.9 f ce . Readers are referred to Thorne et al (2010) (Roux et al, 2011). Using the KAW dispersion relation in Roux et al (2011) with observed local plasma parameters, we estimate that, to be able to interact with ∼ 100 eV electrons via Landau resonance, k ⊥ must be on the order of ∼ 0.1 km −1 .…”
Section: April 2009 Eventmentioning
confidence: 99%
“…Readers are referred to Thorne et al (2010) (Roux et al, 2011). Using the KAW dispersion relation in Roux et al (2011) with observed local plasma parameters, we estimate that, to be able to interact with ∼ 100 eV electrons via Landau resonance, k ⊥ must be on the order of ∼ 0.1 km −1 . With the observed flow magnitudes of several tens of km s −1 , had such short-scale KAW existed, it would have been Doppler-shifted up to ∼ 1 Hz range.…”
Section: April 2009 Eventmentioning
confidence: 99%